QE versus the real problems in the world economy - Adrian Blundell-Wignall (Journal of Risk and Financial Management, 2020)
These notes are based on parts of a keynote address to the Fourth Annual Conference on Money and Finance at Chapman University on 6-7 September 2019. Quantitative easing (QE) policies have been pushed to extremes and extended well beyond their use-by dates to little plausible effect in achieving the goal of raising inflation and growth. Instead, they are damaging the interbank market (as exemplified by the liquidity crisis in September 2019), adding to the risk of financial crises in the future and taking pressure off policy-makers to deal with the real causes of poor investment, growth and deflation pressure. The shift in where investment is occurring and the special problems of Europe and Brexit are focused upon.
Keywords: 330; Brexit; China; Europe; globalization; interbank market; quantitative easing; target 2